2017
DOI: 10.1088/1674-4926/38/11/114006
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric quantum well broadband thyristor laser

Abstract: A broadband thyristor laser based on InGaAs/GaAs asymmetric quantum well (AQW) is fabricated by Metal Organic Chemical Vapor Deposition (MOCVD). The 3-μm-wide Fabry-Perot (FP) ridge-waveguide laser shows an S-shape I-V characteristic and exhibits a flat-topped broadband optical spectrum coverage of ~27 nm (Δ-10 dB) at a center wavelength of ~1090 nm with a total output power of 137 mW under pulsed operation. The AQW structure was carefully designed to establish multiple energy states within, in order to broade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…In Pb-based PSCs, different HTMs affect the efficiency [32,33] and stability of the devices. It has been suggested that dopant-free HTMs are advantageous for device stability,a st he dopantsc an be involved in degradation reactions.…”
Section: Introductionmentioning
confidence: 99%
“…In Pb-based PSCs, different HTMs affect the efficiency [32,33] and stability of the devices. It has been suggested that dopant-free HTMs are advantageous for device stability,a st he dopantsc an be involved in degradation reactions.…”
Section: Introductionmentioning
confidence: 99%